2014
DOI: 10.3390/en7128483
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Radon Detection of Mining-induced Fractures from Overlying Strata to the Surface: A Case Study of the Baoshan Coal Mine in China

Abstract: Large-scale longwall mining of shallow coal seams may cause mining-induced fractures that can project completely through to the surface. This could lead to a series of mine safety and environmental issues, further deteriorating the already fragile ecological environment in the Western mining areas in China. Therefore, an accurate and effective understanding of the spatiotemporal evolution law of mining-induced fractures in overlying strata and its relationship to upper aquifers is critical. In this paper, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…As the shields (hydraulic supports) move, the mine roof behind them continues to cantilever and caves into the mine void, which experiences the process of elastic deformation, plastic deformation, and failure [16,20], producing two types of tensile fractures at the surface over the panel: static tensile fracture above the side of a panel and dynamic tensile fractures that follow behind the advancing face [16,17]. The dynamic tensile fractures close as a result of compressional stress after the advance of the face, and static tensile fractures remain open for several months after mining [17], Currently, a variety of methods, ranging from analytical methods and field experiments to numerical and physical simulation, have been used that mainly focus on the mining-induced effects on the movement of overburden strata, the generation of fractures, and subsidence [2,13,29,30,[45][46][47]. However, very few detailed studies of the caving mechanism of overburden strata have been reported.…”
Section: Fractures Changes Due To Longwall Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…As the shields (hydraulic supports) move, the mine roof behind them continues to cantilever and caves into the mine void, which experiences the process of elastic deformation, plastic deformation, and failure [16,20], producing two types of tensile fractures at the surface over the panel: static tensile fracture above the side of a panel and dynamic tensile fractures that follow behind the advancing face [16,17]. The dynamic tensile fractures close as a result of compressional stress after the advance of the face, and static tensile fractures remain open for several months after mining [17], Currently, a variety of methods, ranging from analytical methods and field experiments to numerical and physical simulation, have been used that mainly focus on the mining-induced effects on the movement of overburden strata, the generation of fractures, and subsidence [2,13,29,30,[45][46][47]. However, very few detailed studies of the caving mechanism of overburden strata have been reported.…”
Section: Fractures Changes Due To Longwall Miningmentioning
confidence: 99%
“…The redistribution of the overburden stress regime caused by longwall mining brings about general increases in fracture porosity and permeability owing to the development of fractures, joints, and bedding separations, resulting in the disruption of the natural groundwater flow system to a great extent [12,15,16,44]. Currently, a variety of methods, ranging from analytical methods and field experiments to numerical and physical simulation, have been used that mainly focus on the mining-induced effects on the movement of overburden strata, the generation of fractures, and subsidence [2,13,29,30,[45][46][47]. However, very few detailed studies of the caving mechanism of overburden strata have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have used endoscopic observations of fractures to describe the quality of rocks, and studied the rock mass stratification [18][19][20]. Zhang et al have proposed the use of on-site radon detection to monitor the evolution of mining-induced fractures in overburden and demonstrated its feasibility through field experiments [21,22]. Applications of these detection techniques and equipment make the analysis of mining-induced CFZ's height easier and more accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, the radon collectors can be taken out from the pits for measurement four hours after placement [33]. During this on-site measurement, each radon collector was embedded in the pit for 24 h and taken out for measurement once per day [34], due to limitations in the field conditions. The coalface kept advancing during the intervals.…”
Section: On-site Measurementmentioning
confidence: 99%